Modern management of ruptured abdominal aortic aneurysm - Scali, Salvatore T.; Stone, David H. (Frontiers in Cardiovascular Medicine, 2023)
Ruptured abdominal aortic aneurysms (rAAA) remain one of the most clinically challenging and technically complex emergencies in contemporary vascular surgery practice.Over the past 30 years, a variety of changes surrounding the treatment of rAAA have evolved including improvements in diagnosis, development of coordinated referral networks to transfer patients more efficiently to higher volume centers, deliberate de-escalation of pre-hospital resuscitation, modification of patient and procedure selection, implementation of clinical pathways, as well as enhanced awareness of certain high-impact postoperative complications. Despite these advances, current postoperative outcomes remain sobering since morbidity and mortality rates ranging from 25%-50% persist among modern published series. Some of the most impactful variation in rAAA management has been fostered by the rapid proliferation of endovascular repair (EVAR) along with service alignment at selected centers to improve timely revascularization. Indeed, clinical care pathways and emergency response networks are now increasingly utilized which has led to improved outcomes contemporaneously. Moreover, evolution in pre-and post-operative physiologic resuscitation has also contributed to observed improvements in rAAA outcomes.Due to different developments in care provision over time, the purpose of this review is to describe the modern management of rAAA, while providing historical perspectives on patient, procedure and systems-based practice elements that have evolved care delivery paradigms in this complex group of patients.